Developing leaders for real : proven approaches that deliver impact - Gimson, Anne; Gray, Harry; Cunningham, Ian (Emerald Publishing Limited, 2022)
The capabilities leaders are required to demonstrate have changed and will no doubt continue to do so. As there is no change without learning, their development experiences are critical. Too many development programmes are preoccupied with defining what leaders should learn, but 'content' is conditioned by dynamic circumstances and in the volatile, uncertain, complex, and ambiguous (VUCA) organizational world, it is rapidly out of date. Developing Leaders For Real: Proven approaches that deliver impact presents chapters from international experts analysing approaches to leadership development that have actually delivered results, capturing how executives at all levels really learn to become better organizational leaders. The chapters: * Share with developers how to create contexts for learning that enable leaders to develop the capabilities needed to thrive in the fast-paced business environment * Provide examples of formal processes of development which have worked in practice * Demonstrate the need for experiential involvement, self-reflection, and a holistic approach.